Increase in Milk Yield from Cows through Improvement of Forage Production Using the N2-Fixing Legume Leucaena leucocephala in a Silvopastoral System - Lucero Sarabia-Salgado; Francisco Solorio-Sánchez; Luis Ramírez-Avilés; Bruno José Rodrigues Alves; Juan Ku-Vera; Carlos Aguilar-Pérez; Segundo Urquiaga; Robert Michael Boddey (Animals, 2020)
The objective was to evaluate milk production, N2-fixation and N transfer, forage yield and composition (under two cutting intervals) in a silvopastoral system (SPS) with Leucaena leucocephala-Megathyrsus maximus and M. maximus-monoculture (MMM) with crossbred cows in a completely randomized design. Forage yield in the SPS was 6490 and 6907 kg DM ha−1 for cutting intervals (CI) of 35 and 50 days. Forage yield for the MMM was 7284 and 10,843 kg DM ha−1, and forage crude protein (CP) was 29.0% and 26.1% for L. leucocephala, harvested at 35 and 50 days, respectively. CP for the associated M. maximus was 9.9% and 7.8% for CI 35 and 50 days, respectively, and for MMM was 7.4% and 8.4%, harvested at 35 and 50 days. Milk production was 4.7 kg cow−1 day−1 for cows grazing MMM and 7.4 kg cow−1 day−1 under SPS. Nitrogen fixation in L. leucocephala (%Ndfa) was estimated to be 89% and 95%, at 35 and 50 days, with an N2 transfer to the associated grass of 34.3% and 52.9%. SPS has the potential to fix and transfer important amounts of N2 to the associated grass, and increase forage CP content and milk production.